Biochemical, structural and functional diversity between two digestive alpha-amylases from helicoverpa armigera - Bhide, Amey J.; Channale, Sonal M.; Patil, Sucheta S.; Gupta, Vidya S.; Ramasamy, Sureshkumar; Giri, Ashok P. (Biochimica Et Biophysica Acta-General Subjects, 2015)
Background: Helicoverpa armigera (Lepidoptera) feeds on various plants using diverse digestive enzymes as one of the survival tool-kit. The aim of the present study was to understand biochemical properties of recombinant alpha-amylases of H. armigera viz., HaAmy1 and HaAmy2. Methods: The open reading frames of HaAmy1 and HaAmy2 were cloned in Pichia pastoris and expressed heterologously. Purified recombinant enzymes were characterized for their biochemical and biophysical attributes using established methods. Results: Sequence alignment and homology modeling showed that HaAmy1 and HaAmy2 were conserved in their amino acid sequences and structures. HaAmy1 and HaAmy2 showed optimum activity at 60 degrees C; however, they differed in their optimum pH. Furthermore, HaAmy2 showed higher affinity for starch and amylopectin whereas HaAmy1 had higher catalytic efficiency. HaAmy1 and HaAmy2 were inhibited to the same magnitude by a synthetic amylase inhibitor (acarbose) while wheat amylase inhibitor showed about 2-fold higher inhibition of HaAmy1 than HaAmy2 at pH 7 while 6-fold difference at pH 11. Interactions of HaAmy1 and HaAmy2 with wheat amylase inhibitor revealed 2:1 stoichiometric ratio and much more complex interaction with HaAmy1. Conclusions: The diversity of amylases in perspective of their biochemical and biophysical properties, and their differential interactions with amylase inhibitors signify the potential role of these enzymes in adaptation of H. armigera on diverse plant diets. General significance: Characterization of digestive enzymes of H. armigera provides the molecular basis for the polyphagous nature and thus could assist in designing future strategies for the insect control. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: alpha-amylases; Amylase inhibitors; Digestive enzymes; Enzyme activity; Helicoverpa armigera

Characterization of two coleopteran alpha-amylases and molecular insights into their differential inhibition by synthetic alpha-amylase inhibitor, acarbose - Channale, Sonal M.; Bhide, Amey J.; Yadav, Yashpal; Kashyap, Garima; Pawar, Pankaj K.; Maheshwari, V. L.; Ramasamy, Sureshkumar; Giri, Ashok P. (Insect Biochemistry and Molecular Biology, 2016)
Post-harvest insect infestation of stored grains makes them unfit for human consumption and leads to severe economic loss. Here, we report functional and structural characterization of two coleopteran alpha-amylases viz. Callosobruchus chinensis alpha-amylase (CcAmy) and Tribolium castaneum alpha-amylase (TcAmy) along with their interactions with proteinaceous and non-proteinaceous alpha-amylase inhibitors. Secondary structural alignment of CcAmy and TcAmy with other coleopteran alpha-amylases revealed conserved motifs, active sites, di-sulfide bonds and two point mutations at spatially conserved substrate or inhibitor binding sites. Homology modeling and molecular docking showed structural differences between these two enzymes. Both the enzymes had similar optimum pH values but differed in their optimum temperature. Overall, pattern of enzyme stabilities were similar under various temperature and pH conditions. Further, CcAmy and TcAmy differed in their substrate affinity and catalytic efficiency towards starch and amylopectin. HPLC analysis detected common amylolytic products like maltose and maltotriose while glucose and malto-tetrose were unique in CcAmy and TcAmy catalyzed reactions respectively. At very low concentrations, wheat alpha-amylase inhibitor was found to be superior over the acarbose as far as complete inhibition of amylolytic activities of CcAmy and TcAmy was concerned. Mechanism underlying differential amylolytic reaction inhibition by acarbose was discussed. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Acarbose; alpha-amylase; alpha-amylase inhibitor; Callosobruchus chinensis; Coleoptera; Tribolium castaneum

Genomic and functional characterization of coleopteran insect-specific alpha-amylase inhibitor gene from amaranthus species - Bhide, Amey J.; Channale, Sonal M.; Yadav, Yashpal; Bhattacharjee, Kabita; Pawar, Pankaj K.; Maheshwari, V. L.; Gupta, Vidya S.; Ramasamy, Sureshkumar; Giri, Ashok P. (Plant Molecular Biology, 2017)
The smallest 32 amino acid alpha-amylase inhibitor from Amaranthus hypochondriacus (AAI) is reported. The complete gene of pre-protein (AhAI) encoding a 26 amino acid (aa) signal peptide followed by the 43 aa region and the previously identified 32 aa peptide was cloned successfully. Three cysteine residues and one disulfide bond conserved within known alpha-amylase inhibitors were present in AhAI. Identical genomic and open reading frame was found to be present in close relatives of A. hypochondriacus namely Amaranthus paniculatus, Achyranthes aspera and Celosia argentea. Interestingly, the 3'UTR of AhAI varied in these species. The highest expression of AhAI was observed in A. hypochondriacus inflorescence; however, it was not detected in the seed. We hypothesized that the inhibitor expressed in leaves and inflorescence might be transported to the seeds. Sub-cellular localization studies clearly indicated the involvement of AhAI signal peptide in extracellular secretion. Full length rAhAI showed differential inhibition against alpha-amylases from human, insects, fungi and bacteria. Particularly, alpha-amylases from Helicoverpa armigera (Lepidoptera) were not inhibited by AhAI while Tribolium castaneum and Callosobruchus chinensis (Coleoptera) alpha-amylases were completely inhibited. Molecular docking of AhAI revealed tighter interactions with active site residues of T. castaneum alpha-amylase compared to C. chinensis alpha-amylase, which could be the rationale behind the disparity in their IC50. Normal growth, development and adult emergence of C. chinensis were hampered after feeding on rAhAI. Altogether, the ability of AhAI to affect the growth of C. chinensis demonstrated its potential as an efficient bio-control agent, especially against stored grain pests.